P65 Elevated numbers and size of aggregates of immune cells protects against liver cancer progression. (28th September 2020) - Cottingham, Sam Wanders; Mauricio-Muir, Joao; McCain, Misti Vanette; Watson, Robyn; Evans, Catriona; Wilson, Caroline; Burt, Alastair; Mann, Derek; Shukla, Ruchi; Reeves, Helen
Abstract : Background: Deaths from hepatocellular carcinoma (HCC) are rising. HCC typically develops in the setting of inflammation and chronic liver disease, where the immune environment can either promote or suppress cancer growth. Immune cells infiltrate within HCC are also suspected to play a key role in determining patient responses to treatments, but this is poorly understood. As the therapeutic options for patients with advanced HCC are changing, with a small minority (<15%) responding dramatically to immune checkpoint (PD-1/PD-L1) inhibition, the need to understand the complexities of the immune environment in liver cancers and develop strategies to improve survival for more patients, is ever more pressing. Methods: Surplus tissues from 58 patients with HCC undergoing diagnostic biopsy, presenting to the Newcastle upon Tyne Hospitals NHS Foundation Trust and recruited to our using SPSS statistical software package, with statistical significance considered as p<0.05 ethically approved CRUK funded research programme, underwent automated immunohistochemistry (Ventana) with antibodies to PD-1 and the neutrophil marker CD66b. Digital images were analysed using the Aperio Leica system paired with ImageScope software. The presence, size and numbers per mm 2 of rounded aggregates of immune cells in tumours were defined and clinicopathological associations explored using SPSS statistical software package, with statistical significance considered as p<0.05. Median values defined 'high' versus 'low' categories. Results: Immune aggregates were detected in HCC in 28/58 patients. Simple 'presence' was not significantly associated with any clinicopathological features. However, higher number mm 2 aggregates (n=14) was associated with less advanced TNM stage (p=0.015), longer time to radiological progression (20.9 vs 8.0 months, Kaplan-Meier, p=0.033) and longer survival (34.0 vs 20.9 months, p=0.024) compared to lower or absent cases (n=44). Furthermore, mean aggregate area correlated negatively with tumour size (Spearmans Rho -0.413, p=0.029). Patients with larger aggregates were more likely to have a maximal tumour diameter <5 cm (13/14 versus 21/44; Chi Square p=0.006). The majority of aggregates (89%) regardless of size had detectable PD-1 expression, which awaits post pandemic characterisation. Patients with larger aggregates were more likely to have high intratumoral CD66b positive neutrophils (8/12 versus 10/37; Chi square p= 0.013). Conclusion: Higher numbers and size of immune aggregates were associated with delayed tumour progression, highlighting the need to further define the tumour immune environment in patients with HCC.